2011
DOI: 10.3390/cancers3022516
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Pathways in Photodynamic Therapy of Cancer

Abstract: Photodynamic therapy (PDT) is an emerging cancer therapy that uses the combination of non-toxic dyes or photosensitizers (PS) and harmless visible light to produce reactive oxygen species and destroy tumors. The PS can be localized in various organelles such as mitochondria, lysosomes, endoplasmic reticulum, Golgi apparatus and plasma membranes and this sub-cellular location governs much of the signaling that occurs after PDT. There is an acute stress response that leads to changes in calcium and lipid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
505
0
41

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 587 publications
(569 citation statements)
references
References 122 publications
23
505
0
41
Order By: Relevance
“…Since there are several processes involved in causing PDT induced cell killing it is not surprising that any of the three commonly known cell death mechanisms, namely apoptosis, necrosis or autophagy can be triggered [5,10,23,26,54]. Confocal microscopy and Förster Resonance Energy Transfer (FRET) imaging on cultured cells demonstrated that common PDT PSs are found to localize in different subcellular structures such as the plasma membrane (Photofrin®), mitochondria (phthalocyanine Pc4), lysosomes, nucleus, endoplasmic reticulum or the Golgi apparatus [5,23,26,43,55].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Since there are several processes involved in causing PDT induced cell killing it is not surprising that any of the three commonly known cell death mechanisms, namely apoptosis, necrosis or autophagy can be triggered [5,10,23,26,54]. Confocal microscopy and Förster Resonance Energy Transfer (FRET) imaging on cultured cells demonstrated that common PDT PSs are found to localize in different subcellular structures such as the plasma membrane (Photofrin®), mitochondria (phthalocyanine Pc4), lysosomes, nucleus, endoplasmic reticulum or the Golgi apparatus [5,23,26,43,55].…”
Section: Figurementioning
confidence: 99%
“…Type III PSs are usually Antioxidant Carrier Sensitizers (ACS), also called Modified Type I (MTO) PSs, which combine properties leading to the efficient generation of singlet oxygen and decreasing the concentration of native free radicals in malignant cells. ACS are usually synthesized from the molecular backbone of originally active PSs used in clinical PDT, such as substituted porphyrin derivatives [5,10,15,17,19,24,26,28,29,[40][41][42][43][44]. Currently novel types of pro-drugs such as combretastatins, discussed fully in section 4.4, are emerging which can be directly photo- activated by multiphoton excitation without the need for the presence of oxygen within the target tissue (see the section on Alternative Strategy for Two-photon Phototherapy (2P-PDT) without ROS below).…”
Section: Photochemistry Of Photosensitizersmentioning
confidence: 99%
“…O tipo de morte celular desencadeado pela TFD irá depender de vários fatores, entre eles: as características químicas do fotossensibilizador, sua concentração e o tempo de incubação com o mesmo, a dose de luz e o tipo celular (Mroz et al, 2011).…”
Section: Morte Celular Induzida Pela Terapia Fotodinâmicaunclassified
“…Elevadas doses de luz ou altas concentrações de fotossensibilizador tendem a causar a morte celular por necrose (Mroz et al, 2011). As características morfológicas da morte por necrose compreendem o aumento do volume celular, a vacuolização do citoplasma e o rompimento da membrana plasmática (Edinger e Thompson, 2004).…”
Section: Morte Celular Induzida Pela Terapia Fotodinâmicaunclassified
See 1 more Smart Citation